Motivation in learning English among the second-year students in Faculty of Banking and Finance, Hanoi University of Business and Technology - Nguyễn, Thị Xuyến (ĐHNN, 2017)
However, there are not any researches conducted to investigate into the situation of students' motivation in learning English at Hubt in general and students in FoBF in particular. All of the above - mentioned reasons have urged the researcher to conduct the research with the title " Motivation in learning English among the second-year students in Faculty of Banking and Finance, Hanoi University of Business and Technology